Practices as the new fundamental social formation in the knowledge society - Turner, Stephen P. (Družboslovne razprave, 2008)
The author analyses the concept of practices which has only recently come to prominence in social theory. The 'rules' or 'norms' model of society is a misleading abstraction and 'practices' better captures the fact that living in society is not simply a matter of rules but of the practical mastery of the cues and expectations of others. The locus of explanation shifts from culture as a determinant in the social system to a more pragmatic understanding of the ongoing effects of practices. Practices are becoming distinctive units of social grouping in the knowledge society.
Keywords: Social theory; Teorija družbe; Znanje; Knowledge; Kognitivna znanost; Cognitive science; Civil society; Civilna družba; znanost; science; družba znanja